An overview of transboundary animal diseases of viral origin in South Asia: What needs to be done? - Gongal, G.; Rahman, Habibar; Thakuri, K.C.; Kennady, Vijayalakshmy (MDPI, 2022)
Transboundary animal diseases (TADs) pose a serious threat to the sustainability and economic viability of the existing animal agriculture ecosystem in south Asia. The rapid spread of African swine fever and lumpy skin diseases in south Asia must be considered a wake-up call to prevent the entry, spread, and establishment of new exotic TADs, as south Asia has the highest density of livestock populations, and it will have a huge socioeconomic impact. Regional cooperation for the prevention and control of TADs is necessary, but rational decisions should be made to initiate even sub-regional cooperation in the present geopolitical situation. Cross-border collaboration for surveillance, early warnings, and animal movement control should be encouraged on a bilateral or multilateral basis as many countries share a porous border. Foot-and-mouth disease (FMD), peste des petits ruminants (PPR), and avian influenza (AI) have been identified as regional priority TADs, and many regional and country initiatives have been undertaken in the last two decades that need to be translated into action. The incursion of exotic TADs into south Asia has compelled us to rethink overall policies and strategies for prevention and control of TADs. This paper took into consideration six emerging and endemic TADs of viral origin to suggest a future course of action.